Some boundary-value problems for a class of fourth-order differential equations on a graph - Mustafokulov, R. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study the problem of nondegeneracy of some boundary-value problems for a class of fourth-order differential equations on a geometric graph (topological net), present conditions for the existence of the Green function for boundary-value problems under consideration, and analyze its principal properties.